Procedures for the Quantitative Determination of Autoprothrombin C - Cole, Edmond R; Marciniak, Ewa; Seegers, Walter H (Thrombosis and Haemostasis, 1962)
Two quantitative procedures for autoprothrombin C are described. In one of these purified prothrombin is used as a substrate, and the activity of autoprothrombin C can be measured even if thrombin is in the preparation. In this procedure a reaction mixture is used wherein the thrombin titer which develops in 20 minutes is proportional to the autoprothrombin C in the reaction mixture. A unit is defined as the amount which will generate 70 units of thrombin in the standardized reaction mixture. In the other method thrombin interferes with the result, because a standard bovine plasma sample is recalcified and the clotting time is noted. Autoprothrombin C shortens the clotting time, and the extent of this is a quantitative measure of autoprothrombin C activity.